The English Student Problems in Speaking of Fifth Semester at UNIMUDA Sorong - Nurteteng Nurteteng; Agus Setiawan (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research was conducted to analysis the students’ problem in speaking and the cause factor of the students’ speaking problem at fifth semester of English Education Department in UNIMUDA Sorong. This research used descriptive qualitative research design. Fifth semester of English Education Department in UNIMUDA Sorong was chosen by the researcher as sample which consists of 16 students. In collecting data, the researcher used interview, and questionnaire. The data collect were analyzed by reducing the data, presenting the data, taking the conclusion and verification. From the data analysis, the researcher found that the students speaking problem are fear of mistake, shyness, lack of motivation, inhibition, lack of typical knowledge or nothing to say and mother tongue used. The cause factor of the speaking problem are external and internal factor. The internal are intelligence and interest in learning while the external factor is classroom environment.